The Students’ Perspectives in Challenges of English Online Learning During Pandemic at MAN 1 Ngawi - Silvia Umrotun Nafiah; Koesoemo Ratih (Prosiding University Research Colloquium, 2022)
The study aims to identify the challenges of the English online learning process during the pandemic by 10th graders at MAN 1 Ngawi. 10th-grade students of MAN 1 Ngawi were the subjects in the study. The perception of 10th graders regarding the barriers that arise in English learning at MAN 1 Ngawi is the object of this research. In carrying out this study, the researcher uses qualitative descriptive methods. Qualitative data analysis techniques that the researcher used in this study are divided into coding, data reduction, data presentation, and interpretation or withdrawal or conclusions. The study used online questionnaires and interviews to obtain data. The researcher also used triangulation techniques to obtain the validity of the research data. This study shows that the online English learning process experiences challenges faced by 10th-grade students, namely difficulties in understanding learning materials, unstable networks, and errors in E-learning applications. Related to this research, there are several implications, namely: a) to provide suggestions and information for schools and improve insight for learners; b) to add knowledge related to the challenges facing 10th graders in online English learning; c) as a comparison or reflection material to improve the quality of ICT-based learning in the future.